Circulating Aldosterone and Natriuretic Peptides in the General Community: Relationship to Cardiorenal and Metabolic Disease. Issue 1 (January 2015) - Buglioni, Alessia; Cannone, Valentina; Cataliotti, Alessandro; Sangaralingham, S. Jeson; Heublein, Denise M.; Scott, Christopher G.; Bailey, Kent R.; Rodeheffer, Richard J.; Dessì-Fulgheri, Paolo; Sarzani, Riccardo; Burnett, John C.
Abstract : We sought to investigate the role of aldosterone as a mediator of disease and its relationship with the counter-regulatory natriuretic peptide (NP) system. We measured plasma aldosterone (n=1674; aged≥45 years old) in a random sample of the general population from Olmsted County, MN. In a multivariate logistic regression model, aldosterone analyzed as a continuous variable was associated with hypertension (odds ratio [OR]=1.75; 95% confidence interval [CI]=1.57–1.96; P <0.0001), obesity (OR=1.34; 95% CI=1.21–1.48; P <0.0001), chronic kidney disease (OR=1.39; 95% CI=1.22–1.60; P <0.0001), central obesity (OR=1.47; 95% CI=1.32–1.63; P <0.0001), metabolic syndrome (OR=1.41; 95% CI=1.26–1.58; P <0.0001), high triglycerides (OR=1.23; 95% CI=1.11–1.36; P <0.0001), concentric left ventricular hypertrophy (OR=1.22; 95% CI=1.09–1.38; P =0.0007), and atrial fibrillation (OR=1.24; 95% CI=1.01–1.53; P =0.04), after adjusting for age and sex. The associations with hypertension, central obesity, metabolic syndrome, triglycerides, and concentric left ventricular hypertrophy remained significant after further adjustment for body mass index, NPs, and renal function. Furthermore, aldosterone in the highest tertile correlated with lower NP levels and increased mortality. Importantly, most of these associations remained significant even after excluding subjects with aldosterone levels above the normal range. In conclusion, we report that aldosterone is associated with hypertension, chronic kidney disease, obesity, metabolic syndrome, concentric left ventricular hypertrophy, and lower NPs in the general community. Our data suggest that aldosterone, even within the normal range, may be a biomarker of cardiorenal and metabolic disease. Further studies are warranted to evaluate a therapeutic and preventive strategy to delay the onset and progression of disease, using mineralocorticoid antagonists or chronic NP administration in high-risk subjects identified by plasma aldosterone. Abstract : Supplemental Digital Content is available in the text.